Studi Etnomatematika: Konsep Geometri pada Jajanan Jadul di Pasar Tradisional Ngasem, Yogyakarta - Setiadi, Wisnu (Jurnal PEKA (Pendidikan Matematika), 2025)
The purpose of this study is to know the history of traditional culinary in Ngasem Market while exploring its geometric concept. Traditional cakes, when viewed physically, have various forms that still survive today. Therefore, in order to identify and analyze the ethnomathematics concept contained in the snacks sold, this qualitative study uses an ethnographic approach to traditional snacks in Ngasem Market with data collection techniques of field observation, interviews with traders, and documentation. The results of the study revealed that traditional snacks in Apem, Bakpia, and Wingko cakes are still available in Ngasem Market and have geometric patterns. The findings of the identified patterns are in flat shapes of circles and rectangles and one cylindrical space shape. The results of this study provide hope and recommendations that can be used as a model for learning mathematics outside the classroom which can also trigger students to understand the history of local culinary culture.